THE INFLUENCE OF HOTEL TAX, RESTAURANT TAX, RECLAIMING TAX ON REGIONAL ORIGINAL INCOME IN MAKASSAR CITY REGIONAL REVENUE OFFICE 2017 – 2021 - Sutriani, Sutriani; Yusuf, Marwah; Anwar, Anwar (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2023)
Purpose – This study aims to determine the effect of hotel tax, restaurant tax, advertisement tax on regional original income at the Makassar City Regional Revenue Service for 2017-2021 Design/methodology/approach – The method of data analysis is using multiple linear regression techniques Findings – The results of the study show that partially hotel taxes and advertisement taxes have an effect on the original regional income of the city of Makassar for the 2017-2022 period, while the restaurant tax has no effect on the original income of the city of Makassar Originality – The sample in this study used a total of 60 months from January 2017 to December 2021 Keywords: Hotel Tax, Restaurant Tax, Advertisement Tax, Local Revenue Paper Type Research Result